Borrowed Voices : Writing and Racial Ventriloquism in the Jewish American Imagination - Glaser, Jennifer, 1978- (Book collections on Project MUSE., 2016)
In this provocative new study, Jennifer Glaser examines how racial ventriloquism became a hallmark of late twentieth-century Jewish-American fiction, as Jewish writers asserted that their own ethnicity enabled them to speak for other minorities. Considering works by everyone from Cynthia Ozick to Woody Allen to Michael Chabon, she demonstrates how Jewish-American fiction can help us understand the larger anxieties about identity, authenticity, and authorial voice that emerged in the wake of the civil rights movement.